2020
DOI: 10.1002/bem.22301
|View full text |Cite
|
Sign up to set email alerts
|

No Increased DNA Damage Observed in the Brain, Liver, and Lung of Fetal Mice Treated With Ethylnitrosourea and Exposed to UMTS Radiofrequency Electromagnetic Fields

Abstract: The widespread use of mobile phones and Wi-Fi-based communication devices makes exposure to radiofrequency electromagnetic fields (RF-EMF) unavoidable. Previous experiments have revealed the tumor-promoting effects of non-ionizing RF-EMF in adult carcinogen-treated mice in utero. To extend these investigations, we tested whether these effects are due to the co-carcinogenicity of RF-EMF which would manifest as elevated DNA damage. Similar to previous experiments, pregnant mice were exposed to RF-EMF (Universal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In particular, radiofrequency (RF), which has an EMF with a bandwidth of 3 kHz to 300 GHz, is widely used in everyday life [ 3 ]. Therefore, there is increasing concern over the potential carcinogenic effects of RF exposure [ 32 ]. Previous studies purporting the carcinogenic effects of RF-EMF have suggested two hypotheses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, radiofrequency (RF), which has an EMF with a bandwidth of 3 kHz to 300 GHz, is widely used in everyday life [ 3 ]. Therefore, there is increasing concern over the potential carcinogenic effects of RF exposure [ 32 ]. Previous studies purporting the carcinogenic effects of RF-EMF have suggested two hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…However, Chagnaud et al did not observe such an effect in rats after irradiation with 900 MHz microwaves 55 or 200 μW/cm 2 (75 and 270 mW/kg average whole-body SAR(Specific Absorption Rate), 2 h daily for 2 weeks) [ 37 ]. Moreover, an in vivo study confirmed that RF-EMF exposure to fetal mice did not increase ethylnitrosourea-induced DNA damages in the brain, liver, or lung [ 32 ]. These findings demonstrate that further studies are needed to elucidate the effects of RF-EMF on DNA damage.…”
Section: Discussionmentioning
confidence: 99%